Inflation: Everywhere and Always Differential - Blair Fix (Economics from the Top Down, 2022)
In November 2021, I wrote a post called `The Truth About Inflation'. At the time, inflation fears were heating up. And as usual, mainstream economists were missing the bus. Sure, economists pointed to the consumer price index and said, “Look, it's going up!” But they didn't look under the hood of this index to see the big picture. Despite what economists proclaim, inflation is not a uniform increase in prices. It is an instability in the whole price system. It's now been a year since that post was published, so I thought I'd update the analysis. While much has changed in the global political landscape, the underlying picture of inflation remains the same: it is everywhere and always differential.
Keywords: P1; D3; E31; 330; capital as power; income distribution; inflation